Scenario analysis for low carbon development in Nigeria. Issue 1 (31st December 2016) - Emodi, Nnaemeka Vincent; Entele, Birku Reta; Ogbuagu, Marc Nwosu; Emodi, Chinenye Comfort; Emodi, Adaeze Saratu Augusta; Okoro, Felix Chimezirim
Abstract: This study explores a scenario-based analysis of future energy consumption and GHG emissions for Nigeria between 2010 and 2040 using the LEAP model. The impact of different energy policies are analysed for the Nigerian energy system by considering four scenarios: The reference (REF) scenario, the low-carbon moderate (LCM) scenario, the low-carbon advanced (LCA) scenario, and the green optimistic (GO) scenario. By considering aggressive energy policies and strategies from LCM to LCA, and even more aggressive options in the GO scenario, we find that under the REF scenario energy demand is expected to reach 3, 075 PJ and a corresponding increase in GHG emissions of 201.2 Mt Co2e by 2040. More aggressive policy intervention by the Nigerian government, as in the GO scenario, would lead to a decrease in energy demand (2, 249 PJ) and GHG emissions (124.4 Mt Co2e) in 2040. A cost-benefit analysis is also carried out in the study.